1989
DOI: 10.1090/qam/1012271
|View full text |Cite
|
Sign up to set email alerts
|

Geometric nonlinearity: potential energy, complementary energy, and the gap function

Abstract: Abstract. Dual minimum principles for displacements and stresses are well established for linear variational problems and also for nonlinear (and monotone) constitutive laws. This paper studies the problem of geometric nonlinearity. By introducing a gap function, we recover complementary variational principles in the equilibrium problems of mathematical physics. When the gap function is nonnegative those become minimum principles. The theory is based on convex analysis, and the applications made here are to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
183
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(185 citation statements)
references
References 6 publications
1
183
0
1
Order By: Relevance
“…This theory was developed originally from Gao and Strang's work in nonconvex mechanics [21] and has been applied successfully for solving a large class of challenging problems in both nonconvex analysis/mechancis and global optimization, such as phase transitions in solids [23], post-buckling of large deformed beam [38], nonconvex polynomial minimization problems with box and integer constraints [13,15,18], Boolean and multiple integer programming [6,40], fractional programming [7], mixed integer programming [20], polynomial optimization [14], high-order polynomial with log-sum-exp problem [3]. A comprehensive review on this theory and breakthrough from recent challenges are given in [19].…”
Section: Canonical Duality Theory and Goalmentioning
confidence: 99%
“…This theory was developed originally from Gao and Strang's work in nonconvex mechanics [21] and has been applied successfully for solving a large class of challenging problems in both nonconvex analysis/mechancis and global optimization, such as phase transitions in solids [23], post-buckling of large deformed beam [38], nonconvex polynomial minimization problems with box and integer constraints [13,15,18], Boolean and multiple integer programming [6,40], fractional programming [7], mixed integer programming [20], polynomial optimization [14], high-order polynomial with log-sum-exp problem [3]. A comprehensive review on this theory and breakthrough from recent challenges are given in [19].…”
Section: Canonical Duality Theory and Goalmentioning
confidence: 99%
“…This nomenclature was introduced first by Gao and Strang in the general context of geometric nonlinearity [14].…”
Section: Conjugate Energy and The Gap Functionalmentioning
confidence: 99%
“…with L r c a quadratic operator of vector d. It will be shown that, under this assumption, two dual extremum principles can be formulated following Gao and Strang's approach [14].…”
Section: Application Of Gao and Strang's Approach To The Derivation Omentioning
confidence: 99%
See 2 more Smart Citations